(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
To understand the image of Amir Temur, it is necessary to take into account the historical context and ideological attitudes of the eras in which literary works were created. The Soviet period (1920s–1980s) was generally characterized by a biased attitude toward medieval monarchs. Marxist-Leninist doctrine viewed the feudal era through the prism of class struggle, and conquerors were seen as embodiments of expansion and reaction.